A highly selective fluorescent indicator for copper based on a boron complex. (1st January 2015) - Zheng, Jie; Huang, Fang; Li, Yujin; Ye, Qing; Jia, Jianhong; Han, Liang; Gao, Jianrong
Condensation of 4-(diethylamino)salicylaldehyde with aqueous hydrazine, followed by complexation with BF3·OEt2 gives a fluorescent indicator highly selective for copper. The indicator forms a 2 : 1 complex with Cu2+ and displays a highly sensitive and selective fluorescent quenching action with Cu2+ upon excitation at 440 nm in water/THF (7 : 3, v/v) solution. This action is pH-independent over the range 4.5 < pH < 9.5.